As duas faces de Jano dos Tribunais de Contas Brasileiros no auxílio ao exercício do controle social sobre a administração pública - Rocha, Diones Gomes da (2017)
For many critics, democracy is a utopian enterprise. More moderate observers, on their turn, propose enhancements for the democratic models of contemporary societies. One of these proposals is to increase citizen insertion in the public sphere, so citizens may participate in State decisions and control the actions of public representatives. The literature has also shown that the process of elections is not enough to guarantee that political representatives will act in the best interest of their constituencies. To attain this aim, it would be necessary to reduce both the information asymmetries between State and society, and the distance between representatives and constituencies. Bearing this context in mind, the relevance of the Courts of Accounts must be highlighted, since they are autonomous and independent institutions that can become important instruments for enhancing the control that society must or should exert over its political representatives. But are these Courts prepared to play this leadership role, considering that they would need to be permeable to society while providing mechanisms to help and facilitate the exercise of social accountability over the public administration? Based on this premise, the aim of this work is to assess the permeability of Brazilian Courts of Accounts to the society, and whether these courts are working to facilitate the exercise of social accountability over the public administration. This descriptive research was developed in two stages. The first stage was a review of the theoretical literature on the theme, to build a framework for assessing the permeability of the Courts of Accounts to the society and their potential for enabling social control. This stage was followed by exercises of Multidimensional Scaling (MDS) that produced perceptual maps of similarities and dissimilarities among the Courts of Account based on the explored factors and indicators. Finally, a round of interviews was carried out with Councilors from the three Courts of Accounts found to be the most similar, and also from the three most dissimilar ones. The results generally show that Brazilian Courts of Accounts are still poorly permeable to society and count on few mechanisms to help and facilitate citizen control. They also show that the means of social participation are still limited, and are basically represented by the Office of the Ombudsman, the Transparency Web Portal and the Citizen Assistance Service. Yet, this study has identified a strong influence of the Fiscal Responsibility Law (LRF) and the Access to Information Law (LAI) at the Courts of Accounts. Although gradually, these elements can lead to future changes in terms of an increasingly prominent role of the Courts of Accounts as strong allies in the process of enhancing vertical accountability.